Implementasi Pengelolaan Surat Masuk dan Keluar di Badan Pemeriksa Keuangan Republik Indonesia - Purwandari, Bella Syafira (Program Studi Pendidikan Ekonomi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Prof. DR. HAMKA, 2017)
The objective of this research was to know the correspondence management applied in the Audit Board of the Republic of Indonesia, which covered the management of incoming and outgoing mail. The effective management of the letter is expected in managing the letter, both incoming mail and outgoing mail. The results were expected to contribute to the improvement and development of the management of the letter. This research was use descriptive qualitative method. The informants were chased purposefully from the staffs. The data collected mostly through participated observation techniques, interviews, documentation analysis. The triangulation techniques used as data validation process for qualitative research. The results of this study indicated that the management of incoming mails was divided into six stages which include: letter receipt, letter ordering, letter briefing, letter recording, mail distribution and mail storage. As for the management of outgoing mail there were also six stages included: the drafting of letters, letter typing, letter editing, the affixing mailing address process, folding and mailing and mail distribution and distribution. The application ran well, and on progress to relocate to electronic mailing system.